Profitability, Company Sizes, Number Of Audit Committe, And Size Of KAP On Audit Delay (Empirical studies in property and real estate companies listed on the Indonesia Stock Exchange in 2014 - 2018) - Mawardani, Audina Ria; Pesudo, David Adechandra (Jurnal Ekonomi Kuantitatif Terapan, 2020)
This study to describe the influence of Profitability, Company Size, Number of Audit Committees, and KAP Size on audit delay both partially and simultaneously on audit delay on Property and Real Estate companies in 2014-2018. The sampling technique used was purposive sampling. The samples in this study were 36 companies in the Property and Real Estate sector which were listed on the Indonesia Stock Exchange in 2014-2018, so that the research data amounted to 180. In this study using descriptive statistical analysis techniques, classic assumption test, and panel data regression analysis. The results of this study indicate that profitability and company size have a significant effect on audit delay, while for the number of audit committees, KAP size has no significant effect on audit delay. Silmultically that profitability, company size, number of audit committees, and KAP Size significantly influence the audit delay of property and real estate companies in 2014-2018.